2009
DOI: 10.5661/bger-26-179
|View full text |Cite
|
Sign up to set email alerts
|

Synthesizing Neurophysiology, Genetics, Behaviour and Learning to Produce Whole-Insect Programmable Sensors to Detect Volatile Chemicals

Abstract: Insects have extremely sensitive systems of olfaction. These systems have been explored as potential sensors for odourants associated with forensics, medicine, security, and agriculture application. Most sensors based on insect olfaction utilize associative learning to "program" the insects to exhibit some form of behavioural response to a target odourant. To move to the next stage of development with whole-insect programmable sensors, an examination of how odourants are captured, processed and used to create … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 146 publications
(97 reference statements)
0
2
0
Order By: Relevance
“…This structure is also covered with a large number of cone-shaped spines, which further increase its adhesion to provide greater attachment during the expression of pre-spawning behaviour [ 32 , 35 , 36 ]. Some studies have shown through electrophysiological experiments that there are contact chemical sensilla on the legs of insects, which can not only perceive salt, water, sugar, and alkaloids [ 37 , 38 ] but also perceive the host extract [ 39 ] and act as a spawning stimulator [ 40 ]. Through ultramicrostructural observation, it was found that the sawtooth-shaped rigid discs are tapered to a point, which is very similar to the shape of the spore sensillum (SG) on the ovipositor [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…This structure is also covered with a large number of cone-shaped spines, which further increase its adhesion to provide greater attachment during the expression of pre-spawning behaviour [ 32 , 35 , 36 ]. Some studies have shown through electrophysiological experiments that there are contact chemical sensilla on the legs of insects, which can not only perceive salt, water, sugar, and alkaloids [ 37 , 38 ] but also perceive the host extract [ 39 ] and act as a spawning stimulator [ 40 ]. Through ultramicrostructural observation, it was found that the sawtooth-shaped rigid discs are tapered to a point, which is very similar to the shape of the spore sensillum (SG) on the ovipositor [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Emerging information about insect olfactory detection abilities and learning abilities revealed that insect olfactory systems are potentially useful tools for the quantitative and qualitative analysis of odorants. 16,124,125 Thus, some insect-sniffers were trained to detect chemicals associated with medicine, security, forensics, agriculture, and food safety applications. Compared to sniffer dogs, an insect sniffer system might be low-cost and could be conditioned with impressive speed for specific chemical detection tasks.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%